FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU PEMBERIAN IMUNISASI RUTIN DALAM PENCEGAHAN PNEUMONIA DI KELURAHAN TANDANG - Ernawati Ernawati; Emmy Riyanti; Ratih Indraswari (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Pneumonia is one of the major killer around toddlers, more than opportunistic infectious disease on AIDS, malaria and measles. One of the pneumonia preventive action is by giving BCG, DPT, Polio, HB, measles and Hib immunizations. The purpose of this research was to analyze the correlation of age, education, occupation, knowledge, attitude, ease of access, husband support, and health officer support with routine immunization behavior on preventing pneumonia in Tandang Regency. This research was an analytical descriptive with cross sectional approach. The research population were mothers with pneumonia child aged 2 - 4 years. Sampling technique was using total population which were 73 respondents. The results of the research with univariate analysis are most adolescence (56,7%), basic-education(55,2%), work (50,7%), good knowlwdge (79,1%), good attitude (56,7%), difficult of access (56,7%), husband support (52,2%),and health officer support (67,2%). The results with Fisher’s Exact Test showed that there were correlations of health officer support (p=0,032) with routine behavior immunization on preventing pneumonia. While age (p=0,574), education (p=0,583), occupation (p=0,614), knowledge (p=1,000), attitude (p=0,574) ease of access (p=0,076) and husband support (p=1,000) had no correlation with routine behavior immunization on preventing pneumonia. It can be concluded that there were meaningful correlation in ease of access and health officer support with routine behavior immunization on preventing pneumonia in Tandang Regency. This research recommended community to give complete routine immunization when baby was having fever, diarrhea, and light illness also health officer should increase information about Hib immunization and increase community knowledge.